Assessment of Carotid Artery Stenosis and the Use of Statins - Whayne, Thomas F., Jr (International Journal of Angiology, 2015)
General thinking has previously centered on managing carotid artery stenosis (CAS) by carotid endarterectomy and subsequently, stenting for higher risk patients. However for CAS and other forms of vascular disease, especially when asymptomatic, there is new emphasis on defining underlying mechanisms. Knowledge of these mechanisms can lead to medical treatments that result in possible atherosclerotic plaque stabilization, and even plaque regression, including in the patient with CAS. For now, the key medication class for a medical approach are the statins. Their use is supported by good cardiovascular clinical trial evidence including some directed carotid artery studies, especially with a demonstrated decrease in carotid intima-media thickness. Procedural controversy still exists but the current era in medicine offers significant support for medical management of asymptomatic CAS while techniques to recognize the vulnerable plaque evolve. If CAS converts to a symptomatic status, early referral for endarterectomy or stenting is indicated.
Keywords: atherosclerosis; cardiovascular risk; carotid artery stenosis; coronary heart disease; peripheral arterial disease; peripheral vascular disease; prevention; statins